Patient Perspectives on Hospital Falls Prevention Education - Hazel Heng; Susan C. Slade; Dana Jazayeri; Cathy Jones; Anne-Marie Hill; Debra Kiegaldie; Debra Kiegaldie; Ronald I. Shorr; Ronald I. Shorr; Meg E. Morris; Meg E. Morris (Frontiers Media S.A., 2021)
Hospital falls remain an intractable problem worldwide and patient education is one approach to falls mitigation. Although educating patients can help their understanding of risks and empower them with prevention strategies, patient experiences of hospital falls education are poorly understood. This study aimed to understand the perspectives and preferences of hospitalized patients about falls prevention education. Three focus groups were conducted in Australian hospitals. A phenomenological approach was used to explore patient perspectives and data were analyzed thematically. The focus groups revealed that most people did not realize their own risk of falling whilst an inpatient. Experiences of falls prevention education were inconsistent and sometimes linked to beliefs that falls were not relevant to them because they were being cared for in hospital. Other barriers to falls mitigation included poor patient knowledge about hospital falls risk and inconsistencies in the delivery of falls prevention education. A strong theme was that individualized, consistent education, and small interactive groups were helpful.